Identifying Acute Ischemic Stroke with Hemichorea as A Clinical Manifestation: A Case Report - Priya Nugraha; Muhammad Hamdan; Harris Kristanto Soedjono; Putri Permata Valentine (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Focal brain lesions can induce abnormal involuntary movement disorders, including hemichorea, hemiballismus, parkinsonism, myoclonus, dystonia, tremor, and asterixis. The most common cause of focal brain lesions is stroke, followed by trauma, neoplasm, anoxia, vascular malformations, metabolic disease, and multiple sclerosis. Hemichorea-hemiballismus as an initial presentation of acute ischemic stroke is very rare, with an incidence rate of 0.54%. Case Presentation: A 65-year-old male with a past medical history of hypertension and diabetes experienced sudden, involuntary, non-rhythmic, and uncontrollable movements of the left extremity one day before being admitted to the hospital. A non-contrast CT scan of the head revealed acute cerebral infarction on the right basal ganglia. The symptoms of hemichorea improved with the initiation of haloperidol after three days of treatment. Regarding this case, acute ischemic stroke should be considered suppose a patient without hyperglycemia and with sudden onset of hemichorea visits to emergency room.